Recent Progress in Developing Monolithic Perovskite/Si Tandem Solar Cells - Liu, Na; Wang, Lina; Xu, Fan; Wu, Jiafeng; Song, Tinglu; Chen, Qi (Frontiers in Chemistry, 2020)
Monolithic perovskite/Silicon tandem solar cells have reached certified efficiency of 28% in recent years. In this review, we discuss material design for monolithic perovskite/Si tandem solar cells, with the focus on the top-cell development to improve their performance. Firstly, we introduce different types of transparent electrodes with high transmittance and low sheet-resistance used in tandem solar cells. We then discuss the development of the wide-bandgap perovskite absorber for top-cells, especially the strategies to obtain the perovskite layers with good efficiency and stability. In addition, as a special functional layer in tandem solar cells, the recombination layers play an important role in device performance, wherein different configurations are summarized. What`s more, tandem device cost analysis is discussed. This review summarizes the progress of monolithic perovskite/Silicon tandem solar cells in a pragmatic perspective, which may promote the commercialization of this technology.